Pengenalan dan Transformasi Diri dalam Kepemimpinan Kristen Berkarakter - Jacob Daan Engel (Sekolah Tinggi Teologi Berita Hidup, 2022)
This research aims to understand a person's quality in Christian leadership. This research is motivated by the fact of being incapable of Christian leadership. This research uses library research to find the data through the literature and analysis. The finding is to introduce in self – transforming to be a measure for a unique Christian leader with the characters through social interaction, which is communication and relationship.